PUBLIC SERVICE MODEL AND EMPLOYEE WORK EFFECTIVENESS THROUGH A WEBSITE-BASED MANAGEMENT INFORMATION SYSTEM - Zulkifli Sultan (Universitas Islam Negeri Alauddin Makassar, 2023)
Services to the public and work effectiveness experience changes in activities so a management information system needs to be implemented. The purpose of this study was to obtain information on the results of implementing a website-based management information system on public services and the effectiveness of employee work. This study uses a qualitative approach in this case completing the formulation that has been determined, while the data collection method is by interviewing 3 employees who are in charge of running the management information system. Furthermore, interviews were also conducted with 2 people who had used information services. Based on the results of research conducted on informants, it was stated that the website-based management information system that was implemented was not optimal in providing services to the public, while for work effectiveness it was sufficient to make it easier for employees to work. The management information system that is implemented in general makes employee work effectiveness easier, but the service does not meet public needs.